Impact of targeted diabetic retinopathy training for graders in Vietnam and the implications for future diabetic retinopathy screening programmes: a diagnostic test accuracy study. Issue 9 (9th September 2022) - Curran, Katie; Congdon, Nathan; Hoang, Tung Thanh; Lohfeld, Lynne; Nguyen, Van Thu; Nguyen, Hue Thi; Nguyen, Quan Nhu; Dardis, Catherine; Virgili, Gianni; Piyasena, Prabhath; Tran, Huong; Salongcay, Recivall Pascual; et al.
Abstract : Objectives: To compare the accuracy of trained level 1 diabetic retinopathy (DR) graders (nurses, endocrinologists and one general practitioner), level 2 graders (midlevel ophthalmologists) and level 3 graders (senior ophthalmologists) in Vietnam against a reference standard from the UK and assess the impact of supplementary targeted grader training. Design: Diagnostic test accuracy study. Setting: Secondary care hospitals in Southern Vietnam. Participants: DR training was delivered to Vietnamese graders in February 2018 by National Health Service (NHS) UK graders. Two-field retinal images (412 patient images) were graded by 14 trained graders in Vietnam between August and October 2018 and then regraded retrospectively by an NHS-certified reference standard UK optometrist (phase I). Further DR training based on phase I results was delivered to graders in November 2019. After training, a randomised subset of images from January to October 2020 (115 patient images) was graded by six of the original cohort (phase II). The reference grader regraded all images from phase I and II retrospectively in masked fashion. Primary and secondary outcome measures: Sensitivity was calculated at the two different time points, and χ 2 was used to test significance. Results: In phase I, the sensitivity for detecting any DR for all grader groups in Vietnam was low (41.8–42.2%) and improved in phase II after additional training was delivered (51.3–87.2%). The greatest improvement was seen among level 1 graders (p<0.001), and the lowest improvement was observed among level 3 graders (p=0.326). There was a statistically significant improvement in sensitivity for detecting referable DR and referable diabetic macular oedema between all grader levels. The post-training values ranged from 40.0 to 61.5% (including ungradable images) and 55.6%–90.0% (excluding ungradable images). Conclusions: This study demonstrates that targeted training interventions can improve accuracy of DR grading. These findings have important implications for improving service delivery in DR screening programmes in low-resource settings.